Reputation-based secyrity for heterogtneous structurally complex systems - Kussul, O.M. (Проблеми програмування, 2012)
In this paper we present the service-oriented infrastructure within the Wide Area Grid (WAG) project that was carried out within the Working Group on Information Systems and Services of the Committee on Earth Observation Satellites (CEOS). The study focuses on enabling trust for this infrastructure using certificates and reputation-based model. В даній роботі розглянуто сервіс-орієнтовану інфраструктуру обробки супутникових даних, яка розроблена в межах міжнародного проекту Wide Area Grid (WAG) робочої групи WGISS комітету супутникових спостережень CEOS. Розглянуто питання забезпечення довіри в таких структурно-складних системах, зокрема на основі сертифікатів та репутації.